INVESTIGATING ENGLISH MAJOR STUDENTS’ ATTITUDES TOWARDS THE EFFICIENCY OF THE “ENGLISH STUDY SKILLS” COURSE IN BURYIMI UNIVERSITY COLLEGE. - Elmahi, Abdallah; Siddig, Babikir El tigani (IJRDO- Journal of Educational Research, 2016)
— In the field of teaching English as a foreign language, and precisely in teaching general English course, this study reflects theattitudes and perceptions of English language learners towards the ―Study Skill Course‖ provided by the Buryimi University college in theSulyinate of Oman. The study is based on the analysis of 25 questionnaires distributed to first Year College students registered in theEnglish Study Skill course class at the time of the study. The questionnaire, aimed at knowing how the students perceived the EnglishStudy Skill course class at the end of the semester. The study shows that the majority of students feel that they have benefited from theEnglish Study Skill course different domains; yet, many required a clearer outline of the course. Between their fondness for the EnglishStudy Skill course and confusion of its aims, English language students understand their need for the course, and perhaps an extraadvanced one too.